The Effect of Neck Movement Pattern Modifications on Pain and Function in Employed Women with Nonspecific Chronic Neck Pain: A Randomized Clinical Trial - Zohreh Khosrokiani; Amir Letafatkar; Yahya Sokhanguei (Vesnu Publications, 2020)
Introduction: Uncontrolled movement has a significant impact on the development of movement disorders and pain. The purpose of this research was to investigate the effect of neck movement pattern modifications on pain and function in women with nonspecific chronic neck pain. Materials and Methods: For this purpose, women (36.5 ± 5.7 years) with nonspecific chronic neck pain were randomly assigned in the experimental (n = 15) and control (n = 15) groups. Pain and function of the participants were measured before and after the intervention, using visual analog scale (VAS) and Progressive Isoinertial Lifting Evaluation, respectively. The repeated measure analysis of variance and paired t tests were used for data analysis. Results: The neck movement pattern modifications had significant effects on pain (P = 0.001) and function (P = 0.004) in the experimental group. Conclusion: Due to the high reported effect size for neck movement pattern modifications, it is suggested to be used as a supplementary method in improvement of pain and function in women with nonspecific chronic neck pain.